A multi-meteorological comparison for episodes of PM10 concentrations in the Berlin agglomeration area in Germany with the LOTOS-EUROS CTM. (1st January 2021) - Thürkow, M.; Kirchner, I.; Kranenburg, R.; Timmermans, R.M.A.; Schaap, M.
Abstract: Particulate matter (PM) remains as one of the most relevant air-quality concerns in urban environments. The Berlin agglomeration area is still affected by exceedances of the daily limit value of the PM concentration, especially during wintertime PM episodes. In this study, we present test-case studies with the LOTOS-EUROS CTM to improve the representation of PM episodes in the Berlin agglomeration area. A variety of simulations were compared for two winter episodes characterized by cold stagnant conditions, using different meteorological input data (from the European Centre for Medium Weather Forecast (ECMWF) and the Consortium for Small-Scale Modelling-Climate Limited-area Modelling (COSMO-CLM)) and horizontal and vertical resolutions of the LOTOS-EUROS CTM. The LOTOS-EUROS CTM indicates too high mixing from the planetary boundary layer (PBL) to higher layers, leading to an underestimation of the PM mass concentration in the Berlin agglomeration. As major impact factor the mixing layer height (MLH) can be identified. Through applying the COSMO-CLM model the meteorological representation of the PBL and MLH can significantly be improved, whereas sensitivity studies only exhibit a small variation of the PBL meteorology and did not further improve the MLH. As the MLHs of both models are underestimated compared to observations and their derivation is questionable, we advise not to use this quantity any longer in CTMs. By contrast, applying a multi-level approach excluding the MLH, provides a considerable increase in the total PM mass concentration amount. The redistribution and increased nitrate and ammonium concentration can be mentioned as the main culprit. However, the best-fit simulations were obtained for the multi-level configuration fed by COSMO-CLM input data, additionally representing a more realistic urban increment. Highlights: An interface of the LOTOS-EUROS CTM to the COSMO-CLM model was developed. PBL conditions were improved by the COSMO-CLM, but no clear bias correction is evident using different parametrizations. Higher resolved model simulations lead to a more realistic representation of the urban-increment. Impacts on PM mass concentrations of refined vertical layers are much larger compared to the meteorological input-data. Ammonium and Nitrate responded highly sensitive to different simulation set-ups.